Bridging Communication Gaps for Maternal Well-being: Menjembatani Kesenjangan Komunikasi untuk Kesejahteraan Ibu - Khoirotul Qiftiyah; Nurul Azizah (Academia Open, 2024)
This study examines the stress levels of a pregnant woman, Mrs. ARN, living with her in-laws, using the Depression Anxiety Stress Scales (DASS 42). At 18 weeks gestation, Mrs. ARN showed mild stress, normal anxiety, and normal depression levels. Her stress stemmed from poor communication with her mother-in-law, leading to discomfort and emotional distress, which negatively impacted her appetite and well-being. The findings highlight the need for effective adaptation strategies and strong spousal support to create a harmonious living environment, reducing stress and promoting healthy pregnancy outcomes. Highlights: 1. Measurement of Stress: Mrs. ARN's stress, anxiety, and depression were assessed using the DASS 42 scale, revealing mild stress.2. Communication Issues: Poor communication with her mother-in-law was a significant source of Mrs. ARN's stress and emotional discomfort.3. Need for Support: Effective adaptation strategies and spousal support are crucial for reducing stress and ensuring healthy pregnancy outcomes. Keyword: Pregnancy stress, in-laws, DASS 42, spousal support, adaptation strategies